A study of prescription pattern in the drug therapy of acne vulgaris at a tertiary care hospital in Mangalore, India - M., Pooja; Holla, Rajendra; B. S., Girisha; A., Puneeth (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Acne Vulgaris is the most common skin disorder of the pilosebaceous unit with excess sebum production, follicular epidermal hyperproliferation, inflammation and Propionibacterium acnes activity, affecting about 80% of teenagers and has considerable psychological and social consequences and physical disability. Use of established topical and oral drugs assumes paramount importance in the treatment of acne vulgaris. Therefore, periodic auditing of prescription is necessary to increase therapeutic benefit and decrease adverse effects. Aim and objectives of the study was to evaluate the pattern of prescription and its rationale in the drug therapy of acne vulgaris. To monitor the adverse effects, if any. Methods: A prospective, hospital based, observational study. Data was collected for a period of 1 year from January 2015 to December 2015 from the outpatient records in the OPD of Dermatology at Justice K.S. Hegde Charitable Hospital, Deralakatte, Mangalore, in a specifically designed proforma. Results: The prescription data of 346 patients were analyzed of which 45.1% were males with an average age of 21.94±0.3 years. Among the four grades of Acne Vulgaris, Grade II (53.17%) was more prevalent followed by Grade I (26.58%), Grade III (13.87%) and Grade IV (6.35%). The number of drugs prescribed for topical use was 514 of which the most commonly prescribed drugs were Benzoyl Peroxide (19.46%), a combination of Tretinoin and Clindamycin (17.12%), Tretinoin alone (12.45%), Clindamycin alone (10.51%) etc. The number of drugs prescribed for systemic use was 98 consisting of Doxycycline (55.1%), Azithromycin (34.7%), Isotretinoin (6.12%) and Erythromycin (4.08%). Conclusions: There was rationality in most of the prescriptions giving no scope for polypharmacy.